Biocide application for controlling biofouling of SWRO membranes - an overview - Kim, Dooil; Jung, Seunghoon; Sohn, Jinsik; Kim, Hyungsoo; Lee, Seockheon (ELSEVIER SCIENCE BV, 2009)
Biofouling due to microbial growth oil the RO membrane adds significant osmotic pressure and causes frequent chemical cleaning which reduces the life of RO membrane. Biocides such as chlorine, ozone, and UV have been used to control microbial growth correlated to the biological fouling of the RO membrane. Among them, free chlorine is most frequently used but incorporated into membrane damage, disinfection by-product formation, and microorganism out-growth because of the following quenching process using sodium bisulfite. Bromate, formed during ozonation of bromide-rich saline water, is classified as a carcinogen by USEPA and WHO and could limit the usage of treated water as drinking water. UV treatment, however, is gaining its Popularity since it does not produce any by-product, quenches remaining chlorine without using sodium bisulfite, and oxidizes organic matter in the saline water. Regardless of its advantages, it has a scaling issue on the quartz sleeve. Therefore, careful comparisons of the biocides are required for SWRO pretreatment. The purpose of this paper is to Summarize current disinfection practice for SWRO pretreatment to help plant designers to choose an optimal disinfection pretreatment process.
Keywords: REVERSE-OSMOSIS MEMBRANE; EXTRACELLULAR POLYMERIC SUBSTANCES; ASSIMILABLE ORGANIC-CARBON; WASTE-WATER TREATMENT; CHLORINE DIOXIDE; BENCH-SCALE; CONVENTIONAL PRETREATMENT; HYPOCHLORITE DEGRADATION; SEAWATER DESALINATION; UF PRETREATMENT